Web Search Results Personalization - Salim, Sayed Suhel Mohd. (IJRDO -Journal of Computer Science Engineering, 2015)
In the present scenario information can be achieved easily through web. Although search engines provideplenty of data but it has a drawback that the information is not correct. According to research users lack interestif it is time consuming and does not provide accurate data. So search engines must provide accurate data. Sincepersonalized web environments provide exact and instant data both to short term and long term users there is anincrease in its demand. We have given various personalization techniques and approaches in this paper.